Soil-Test-Based Phosphorus Recommendations for Commercial Agricultural Production in Florida - Rao Mylavarapu; Yuncong Li; Maria Silveira; Cheryl Mackowiak; J. Mabry McCray (EDIS)
This new 6-page publication of the UF/IFAS Department of Soil and Water Sciences is intended to address agronomic and environmental issues related to phosphorus (P) dynamics in Florida agricultural soils and soil test P interpretation and management for agricultural crops. This document aims to provide science-based information to agricultural clientele, including commercial producers, small farmers, Extension agents, crop consultants, landscape professionals, representatives of the fertilizer industry, state and local agencies, students and instructors of high schools and colleges, researchers, and interested Florida citizens. Written by Rao Mylavarapu, Yuncong Li, Maria Silveira, Cheryl Mackowiak, and Mabry McCray. https://edis.ifas.ufl.edu/ss699